- Writing and Solving One-Step Equations
- Home
- Solving a One-Step Linear Equation Problem Type 1
- Solving a One-Step Linear Equation Problem Type 2
- Additive Property of Equality With Whole Numbers
- Solving an Equation With Multiplication or Division
- Multiplicative Property of Equality With Whole Numbers
- Translating a Sentence Into a One-Step Equation

# Solving a One-Step Linear Equation Problem Type 1 Online Quiz

Following quiz provides Multiple Choice Questions (MCQs) related to **Solving a One-Step Linear Equation Problem Type 1**. You will have to read all the given answers and click over the correct answer. If you are not sure about the answer then you can check the answer using **Show Answer** button. You can use **Next Quiz** button to check new set of questions in the quiz.

### Answer : D

### Explanation

**Step 1:**

6 = q − 5

Adding 5 to both sides

**Step 2:**

6 + 5 = q – 5 + 5

So, q = 11

### Answer : A

### Explanation

**Step 1:**

9 = k + 5

Subtracting 5 from both sides

**Step 2:**

9 – 5 = k + 5 – 5

So, k = 4

### Answer : B

### Explanation

**Step 1:**

t + 2 = 13

Subtracting 2 from both sides

**Step 2:**

t + 2 – 2 =13 – 2 = 11

So, t = 11

### Answer : C

### Explanation

**Step 1:**

w – 6 = 8

Adding 6 to both sides

**Step 2:**

w – 6 + 6 = 8 + 6 = 14

So, w = 14

### Answer : C

### Explanation

**Step 1:**

x + 5 = 13

Subtracting 5 from both sides

**Step 2:**

x + 5 – 5 = 13 – 5 = 8

So, x = 8

### Answer : B

### Explanation

**Step 1:**

3 + x = 7

Subtracting 3 from both sides

**Step 2:**

3 + x – 3 = 7 – 3 = 4

So, x = 4

### Answer : A

### Explanation

**Step 1:**

9 + p = 16

Subtracting 9 from both sides

**Step 2:**

9 + p – 9 = 16 – 9 = 7

So, p = 7

### Answer : D

### Explanation

**Step 1:**

11 – m = 6

Subtracting 11 from sides

**Step 2:**

11 – m – 11 = 6 – 11 = −5

− m = −5

**Step 3:**

Changing signs on both sides of equation

So, m = 5

### Answer : C

### Explanation

**Step 1:**

8 + z = 19

Subtracting 8 from both sides

**Step 2:**

8 + z – 8 = 19 – 8 = 11

So, z = 11

### Answer : B

### Explanation

**Step 1:**

12 – y = 8

Subtracting 12 from both sides

**Step 2:**

12 – y – 12 = 8 – 12 = − 4

− y = −4

**Step 3:**

Changing signs on both sides of equation

So, y = 4